GAMBARAN PREMARITAL SEXUAL PERMISSIVENESS PADA EMERGING ADULTS DI JAKARTA, BOGOR, DEPOK, TANGERANG, DAN BEKASI - Rastrianez Rastrianez; Dinastuti Dinastuti (MANASA, 2013)
Premarital sexual permissiveness (PSP) is defined by Reiss (1964) as the degree of acceptance of various level of physical intimacy in premarital heterosexual relationship. The purpose of this study is to explore the PSP of emerging adults in Jakarta, Bogor, Depok, Tangerang, and Bekasi. Due to globalization era, it is assumed that emerging adults have more permissive attitude towards premarital sexual behavior and a higher-level PSP than the previous study. Participants of this study are 426 emerging adults, both male and female, heterosexual, and live in Jakarta, Bogor, Depok, Tagerang, or Bekasi, collected by convenience sampling technique. The 52-item Guttman scale for measuring PSP in this study have been tested its validity (.943) and reliability (.868). Using T score, multiple regression and linear regression analysis techniques, this study reports: (a) the PSP level of participants are low, (b) there are 5 variables that significantly effected participant’s PSP, that is male, lived only with father, doing religious rituals, live the teaching of religion, and have a friend (reference group) who had sexual intercourse before marriage, and (c) the PSP cannot be used to predict participants sexual behavior.